Pendampingan Pengendalian Fungi pada Aggur Caru Club Sebagai Upaya Peningkatan Kualitas Hasil Panen: Indonesia - Sukendar, Niken Sylvia Puspitasari; Etica, Use; Rusli, Latiefa; Rohman, Mohamad Alim; Irawan, Feri; Ahdi, Istaufal (UII, 2024)
Diseases in the vine can affect the quality and quantity of grape production. The majority of members of the Caru Wine Club (ACC) still do not know the type of disease in the vine and how to control it. This activity aims to provide assistance in fungal control to ACC partners. The implementation method is through direct assistance to ACC partners in Caru hamlet, Bajang village, Mlarak District, Ponorogo Regency consisting of 22 members. The training stage begins with plant identification, training and practice of making sulfur jaddam fungicides, as well as control by spraying sulfur jaddam fungicides. The results of the training showed that ACC partners were already able to create sulfur jaddam fungicides, identify plants infested with fungi, and spray skills correctly. Spraying is carried out once a week for one month. The impact of this activity proves that grape plants that have been sprayed using the sulfur jaddam fungicide can reduce pests on grape plants. The sulfur jaddam fungicide applied to the vine is able to reduce diseases in the vine so that the vine is quite resistant to disease and thrives. To maximize crop yields, partners need to be disciplined regarding the time of spraying grapes because it will affect the growth of fungi that can damage plants if the spraying of jaddam sulfur fungicide is inconsistent.